Polydatin Prevents Lipopolysaccharide (LPS)-Induced Parkinson's Disease via Regulation of the AKT/GSK3β-Nrf2/NF-κB Signaling Axis - Huang, Bingxu; Liu, Juxiong; Meng, Tianyu; Li, Yuhang; He, Dewei; Ran, Xin; Chen, Guangxin; Guo, Wenjin; Kan, Xingchi; Fu, Shoupeng; Wang, Wei; Liu, Dianfeng (Frontiers in Immunology, 2018)
Parkinson’s disease (PD) is a common neurodegenerative disease characterized by selective loss of dopaminergic neurons in the substantia nigra (SN). Neuroinflammation induced by over-activation of microglia leads to the death of dopaminergic neurons in the pathogenesis of PD. Therefore, downregulation of microglial activation may aid in the treatment of PD. Polydatin (PLD) has been reported to pass through the blood-brain barrier and protect against motor degeneration in the SN. However, the molecular mechanisms underlying the effects of PLD in the treatment of PD remain unclear. The present study aimed to determine whether PLD protects against dopaminergic neurodegeneration by inhibiting the activation of microglia in a rat model of lipopolysaccharide (LPS)-induced PD. Our findings indicated that PLD treatment protected dopaminergic neurons and ameliorated motor dysfunction by inhibiting microglial activation and the release of pro-inflammatory mediators. Furthermore, PLD treatment significantly increased levels of p-AKT, p-GSK-3βSer9, and Nrf2, and suppressed the activation of NF-κB in the SN of rats with LPS-induced PD. To further explore the neuroprotective mechanism of PLD, we investigated the effect of PLD on activated microglial BV-2 cells. Our findings indicated that PLD inhibited the production of pro-inflammatory mediators and the activation of NF-κB pathways in LPS-induced BV-2 cells. Moreover, our results indicated that PLD enhanced levels of p-AKT, p-GSK-3βSer9, and Nrf2 in BV-2 cells. After BV-2 cells were pretreated with MK2206 (an inhibitor of AKT), NP-12 (an inhibitor of GSK-3β), or Brusatol (BT; an inhibitor of Nrf2), treatment with PLD suppressed the activation of NF-κB signaling pathways and the release of pro-inflammatory mediators in activated BV-2 cells via activation of the AKT/GSK3β-Nrf2 signaling axis. Taken together, our results are the first to demonstrate that PLD prevents dopaminergic neurodegeneration due to microglial activation via regulation of the AKT/GSK3β-Nrf2/NF-κB signaling axis.